Magnetic resonance enterography changes after antibody to tumor necrosis factor (anti-TNF) alpha therapy in Crohn's disease: correlation with SES-CD and clinical-biological markers. Issue 1 (December 2016) - Stoppino, Luca; Della Valle, Nicola; Rizzi, Stefania; Cleopazzo, Elsa; Centola, Annarita; Iamele, Donatello; Bristogiannis, Christos; Stoppino, Giuseppe; Vinci, Roberta; Macarini, Luca
Abstract Background In recent years, the use of MRI in patients with Crohn's disease (CD) has increased. However, few data are available on how MRI parameters of active disease change during treatment with anti-TNF and whether these changes correspond to symptoms, serum biomarkers, or endoscopic appearance. The aim of this study was to determine the changes over time in MRI parameters during treatment with anti-TNF in patients with CD, and to verify the correlation between MRI score, endoscopic appearance and clinical-biological markers. Methods We performed a prospective single centre study of 27 patients with active CD (18 males and 9 females; median age of 27, 4 ys; age range, 19–49). All patients underwent ileocolonoscopy and MRI at baseline and 26 weeks after anti-TNF therapy. Endoscopic severity was graded according to the Simple Endoscopic Score for Crohn's Disease (SES-CD) and Magnetic Resonance Index of Activity (MaRIA) was calculated. Patients underwent clinical evaluation (CDAI) and the C-reactive protein (CRP) level was measured. The associations between variables were assessed with Pearson's bivariate correlation analysis. Results A total of 135 intestinal segments were studied. The median patient age was 27, 4 years, 67 % were male and the mean disease duration was 6, 1 years. For induction of remission, 18 patients were treated with infliximab and 9 with adalimumab. The mean SES-CD and MaRIA scores significantly changed at week 26 (SES-CD: 14, 7 ± 8, 9 at baseline vs. 4, 4 ± 4, 6 at 26 weeks -p  < 0.001; MaRIA: 41, 1 ± 14, 8 at baseline vs. 32, 8 ± 11, 7 at 26 weeks -p  < 0.001). Also the CDAI and serum levels of CRP decreased significantly following treatment (p  < 0.001). The overall MaRIA correlated with endoscopic score and with clinical activity (CDAI) both at baseline and at week 26 (p  < 0.05). The correlation between overall MaRIA and CRP was significant only at week 26 (p  < 0.001). Conclusions The MaRIA has a good correlation with SES-CD, a high accuracy for prediction of endoscopic mucosal healing and is a reliable indicator to monitor the use of TNF antagonists in patients with CD.